2012
DOI: 10.1371/journal.pone.0052054
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive Effector/Memory CD4+ and CD8+ T Cells Infiltrating Grafted and Endogenous Islets in Diabetic NOD Mice Exhibit Similar T Cell Receptor Usage

Abstract: Islet transplantation provides a “cure” for type 1 diabetes but is limited in part by recurrent autoimmunity mediated by β cell-specific CD4+ and CD8+ T cells. Insight into the T cell receptor (TCR) repertoire of effector T cells driving recurrent autoimmunity would aid the development of immunotherapies to prevent islet graft rejection. Accordingly, we used a multi-parameter flow cytometry strategy to assess the TCR variable β (Vβ) chain repertoires of T cell subsets involved in autoimmune-mediated rejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…It is widely accepted that diabetogenic T cells are enriched within the pancreatic islets and pLN in NOD mice (8,31). This notion emanates from animal model studies, such as those by Lennon et al, which demonstrated that islet entry and accumulation is an antigen-specific, cell-autonomous event (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that diabetogenic T cells are enriched within the pancreatic islets and pLN in NOD mice (8,31). This notion emanates from animal model studies, such as those by Lennon et al, which demonstrated that islet entry and accumulation is an antigen-specific, cell-autonomous event (7).…”
Section: Resultsmentioning
confidence: 99%
“…A pathogenic role for adaptive immunity is also supported by the development of T1D in recipients of bone marrow transplants from both twin and unrelated T1D donors (4,5). In addition, adoptive transfer experiments in the NOD mouse model support the notion that T cells are both necessary and sufficient for disease development (6) and are retained in pancreatic draining lymph nodes (pLN) prior to and after disease onset (7,8). Hence, there is great interest in monitoring and tracking the T cell repertoire during T1D pathogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…BM was flushed with mouse tonicity PBS/2.5% FCS, erythrocytes were lysed (NH 4 Cl/TRIS buffer), and BM was injected intravenously within 3 h of irradiation (300cGy, 137 Cs source). HSPCs for transfer were prepared by highspeed FACS sorting of lin-negative (lin 2ve )/c-kit-positive (c-kit +ve ) cells to typically .95% purity from bulk BM.…”
Section: Bm Transplantationmentioning
confidence: 99%
“…Pathogenic memory T cells are prominent in type 1 diabetes (T1D), where they arise during the early, preclinical phase of disease and are well established by the time of diagnosis (2). In addition to perpetuating disease, islet-specific CD4 + and CD8 + memory T cells are persistent and may remain dormant for extended periods after T1D onset but are rapidly reactivated by islet antigen exposure during islet transplantation and contribute substantially to rejection of transplanted islets (3,4). Thus, immunotherapy for T1D must address memory T cells regardless of disease stage, and this is crucial for success of islet transplantation.…”
mentioning
confidence: 99%
“…In the NOD mouse, immune responses directed toward insulin are required for diabetes development (French et al, 1997;Nakayama et al, 2005). Insulin-reactive Tmem have been identified in the periphery of patients with T1D (Luce et al, 2011) and in the NOD mouse (Chee et al, 2014;Diz et al, 2012). More importantly, insulin-specific CD8 + T cells have been detected in the pLN and islets in human T1D (Coppieters et al, 2012).…”
mentioning
confidence: 99%